Analisis Anteseden Produktivitas Kerja dan Kepuasan Kerja pada Karyawan Bank di Kepulauan Riau - Farid, Ridhayati; Dzaky, Muhammad Naufal; Qadri, Rizni Aulia; Anggiani, Sarfilianti (Magister Manajemen Universitas Wisnuwardhana, 2024)
The purpose of this study is to analyze the influence of the implementation of e-HRM, the use of technology and information, HR services and the quality of innovation on employee productivity and job satisfaction. This research was conducted on the banking sector in the city of Tanjungpinang, Riau Islands Province, Indonesia. The respondents to this study were 250 who were bank employees in the city of Tanjungpinang. The questions in this research questionnaire are 34 questions that cover all research variables and are filled out through a google form. The research data was processed by analysis using SPSS. The results of this study show that the use of ICT and the quality of innovation used by employees in working have a positive effect on work productivity and job satisfaction. Meanwhile, the implementation of eHRM and the quality of HR services do not have a significant impact on employee work productivity.